Preparation and characterization of eggshell membrane/PVA hydrogel via electron beam irradiation technique - Choi, Jawun; Pant, Bishweshwar; Lee, Chohye; Park, Mira; Park, Soo-Jin; Kim, Hak-Yong (Journal of industrial and engineering chemistry (Seoul, Korea), 2017)
[Display omitted] Eggshell membrane (ESM), which locates between the egg white and the inner surface of the eggshell, is generally considered as waste; however, it can be utilized in various fields. In this contribution, we report a fabrication of ESM based hydrogel by incorporating with polyvinyl alcohol (PVA) via an electron beam irradiation technique. A hydrogel with porous structure along with homogeneous networks was obtained by this ecofriendly approach. The resulting ESM based hydrogels were characterized by using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), and X-ray diffraction (XRD). The swelling analysis of the produced hydrogel showed a super absorption property. This cost effective method eliminates the use of sophisticated equipment’s and toxic chemicals used to fabricate hydrogel for various applications.